Metode Tilawati dalam Pembelajaran Al-Qur’an Di SDI Al-Hidayah Pamulang - Nisma Syifa Fauziah; Fajar Syarif (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2019)
This study aims to find out clearly about the use of the Tilawati method in learning the Qur'an in the Al-Hidayah Pamulang Islamic Elementary School. One of the learning methods is to find out the students' fluency in reading the Qur'an. This research is a descriptive qualitative analysis with a background in Al-Hidayah Pamulang Islamic Elementary School, the research subjects are Grade 3 students. The researcher observes the teacher's activities including the opening of the opening activities, the implementation of the core activities, and the implementation of closing activities. In addition to observing teacher activities, researchers also observed student activities in learning including fluency in reading the Koran of students, the ability to read in accordance with recitation, and the ability of students to recite letters in accordance with their meaning. Based on the results of research conducted by the author at SDI Al-Hidayah Pamulang that the Al-Qur'an learning process using the Tilawati method runs well because the teacher plays an important role in the method so that the results achieved by students are very influential with the competence of the teacher in the delivery of the method.